Preheat and PWHT analysis of FCAW A573 grade 70 welds results of HT and NHT materials on hardness and microstructure - Karim Al Amin, Mochammad; Zakaria, Abdul Majid; Bachtiar, Bachtiar; Rachman, Arif; Widodo, Eriek Wahyu Restu; Fauzi, Muhammad (Journal of Welding Technology, 2024)
Material A573 Grade 70 is one type of material used to manufacture pressure vessel shells or walls. The thickness of the shell depends on the required pressure design for production. In a case study on pressure vessel shell manufacturing, a thickness of 36 mm was used near the manhole. Due to the connection between the shell and the manhole, the material A573 Grade 70 in the shell was subjected to heat influence. The shell near the manhole will be connected to the rest of the shell using the same material, A573 Grade 70. Consequently, it was necessary to analyse the heat treatment for this material. The heat treatments used to determine the microstructure and hardness value were Preheat and Post Weld Heat Treatment (PWHT). Both types of heat treatments were employed. The preheat temperatures varied at 120°C, 150°C, and 200°C for each joint undergoing PWHT at 650°C with a holding time of 60 minutes, as well as for joints without PWHT. The microstructure of variations with preheat and PWHT exhibited finer grains compared to variations without PWHT. The highest recorded hardness value among the variations with PWHT was 209.89 HVN in the weld metal for the 150°C preheat variation. The highest recorded hardness value among the variations without PWHT was 235.07 HVN in the weld metal for the 200°C preheat variation